Implementasi dan Kepatuhan Prinsip Halal pada Produk Farmasi dan Kosmetik - Sindi Setiawati; Mutia Latifa; Andara Safitri Fahiratunisa; Lina Marlina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the implementation and compliance with halal principles in pharmaceutical and cosmetic products in Indonesia. The halal aspect in these industries is crucial, as it directly relates to the permissibility of raw materials, production processes, and distribution that are consumed and used by Muslim communities. The research method applied is a literature review, analyzing government regulations, religious fatwas, and relevant previous studies. The findings indicate that the implementation of halal principles covers various aspects, including the selection of raw materials free from prohibited or impure substances, production processes that meet hygiene and halal standards, proper storage, distribution that is separated from non-halal products, and transparent marketing strategies. Producers’ compliance with halal requirements is influenced by several factors, such as growing consumer awareness, the role of government regulations in mandating halal certification, and corporate social as well as ethical responsibility. Nevertheless, there are still obstacles in its application, including the limited understanding of halal standards among certain producers, the lack of halal testing facilities, and certification costs that are considered burdensome for small and medium-sized enterprises. This study emphasizes that the success of halal implementation in pharmaceutical and cosmetic products requires collaboration among all stakeholders, including government bodies, halal certification authorities, industries, and society. Through such synergistic efforts, the sustainability of the halal industry can be ensured while also providing safety, comfort, and spiritual assurance for Muslim consumers in Indonesia.